ANALISA PEMAKAIAN ALAT BERAT EXCAVATOR DENGAN STRAIGHT LINE DAN REDUCING CHARGE METHOD - Tripoli, Bambang; Febrianti, Dian (Universitas Teuku Umar, 2018)
PT. Gramita Eka Saroja, which is engaged in providing construction services in Meulaboh, West Aceh Regency, has heavy equipment that requires initial investment and a significant operating cost. Technically the existing equipment can still be operated and be able to produce, but it is economically unprofitable. In the case of the issues raised by this study, it is closely related to the estimated cost of owning an excavator heavy equipment so that the company can overcome the problems related to the use of the tool by determining the depreciation and economic value of the tool.. Based on the explanation, the problem and the objective of this research are how much the cost of owning costs must be calculated as long as the equipment is operated from new (purchase) in 2007 to 2018 with the economic life of the excavator heavy equipment is 11 years of use, if it is considered depreciating based on the straight-line method and the depreciation method decreases every year. Based on the calculation of depreciation per year by the straight-line method of Rp. 38,636,364 per year, with working hours Rp. 100,000 per hour / year. In the method of a balanced reduction in depreciation in 2007 Rp. 100,413,223 and in 2018 amounting to Rp. 20,059,008, while the total value of the year produced Rp. 95,764,463 with a 2007 book value of Rp. 187,471,826 and in 2018 amounting to Rp. 8,705,860 with a book value (residual value per year) Rp. 100,413,223. Bank, insurance and tax interest rates are Rp. 18,953 per hour.?